Addressing Cetacean–Fishery Interactions to Inform a Deep-Sea Ecosystem-Based Management in the Gulf of Taranto (Northern Ionian Sea, Central Mediterranean Sea) - Pasquale Ricci (Journal of Marine Science and Engineering, 2021)
Understanding of cetaceans’ trophic role and the quantification of their impacts on the food web is a critical task, especially when data on their prey are linked to deep-sea ecosystems, which are often exposed to excessive exploitation of fishery resources due to poor management. This aspect represents one of the major issues in marine resource management, and trade-offs are needed to simultaneously support the conservation of cetaceans and their irreplaceable ecological role, together with sustainable fishing yield. In that regard, food web models can represent useful tools to support decision-making processes according to an ecosystem-based management (EBM) approach. This study provides a focus on the feeding activity occurrence and the trophic interactions between odontocetes and the fishery in the marine food web of the Gulf of Taranto (Northern Ionian Sea, Central Mediterranean Sea), by zooming in on cetaceans’ prey of commercial interest. In particular, the quantification of trophic impacts is estimated using a food web mass-balance model that integrates information on the bathymetric displacement of both cetaceans’ prey and fishing activity. The results are discussed from a management perspective to guide future research and knowledge enhancement activities as well as support the implementation of an EBM approach.